2018
DOI: 10.1038/labinvest.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear functions of NME proteins

Abstract: The NME family of proteins is composed of 10 isoforms, designated NME1-10, which are diverse in their enzymatic activities and patterns of subcellular localization. Each contains a conserved domain associated with a nucleoside diphosphate kinase (NDPK) function, although not all are catalytically active. Several of the NME isoforms (NME1, NME5, NME7, and NME8) also exhibit a 3′–5′ exonuclease activity, suggesting roles in DNA proofreading and repair. NME1 and NME2 have been shown to translocate to the nucleus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 66 publications
2
63
0
Order By: Relevance
“…Depletion of nucleoside diphosphate kinase A (NME1) lead to a redistribution of eEF1Bα from the cytoplasm to the endoplasmic reticulum fraction in mouse liver (Bruneel et al, 2011). Importantly, nucleoside diphosphate kinase A can be transferred to the nucleus where it promotes the non-homologous end joining of the DNA doublestrand breaks (Xue et al, 2019) and takes part in transcription (Puts et al, 2018).…”
Section: Eef1bαmentioning
confidence: 99%
“…Depletion of nucleoside diphosphate kinase A (NME1) lead to a redistribution of eEF1Bα from the cytoplasm to the endoplasmic reticulum fraction in mouse liver (Bruneel et al, 2011). Importantly, nucleoside diphosphate kinase A can be transferred to the nucleus where it promotes the non-homologous end joining of the DNA doublestrand breaks (Xue et al, 2019) and takes part in transcription (Puts et al, 2018).…”
Section: Eef1bαmentioning
confidence: 99%
“…The homozygous mutation in NME3 gene was found in fatal neurodegenerative disorder [44]. The pro-inflammatory role of NDK3 in signaling downstream of TLR5, had been recognized in cancer immunotherapies [45]. Present study found 1.31 fold increase in protein levels in frail patients in comparison to non-frail patients.…”
Section: Nk Cells Are Necessary For Providing Protection To Normal Cementioning
confidence: 54%
“…[48][49][50][51][52][53][54][55] The interactions of NDPK with components of the cytoskeletal machinery are highly relevant, given the well-established role of the cytoskeleton in cell motility, a critical determinant of the metastasis process. NME1 has also been reported to bind proteins belonging to small and heterotrimeric G-proteins ( [56][57][58][59][60][61] ; and Filic 62 upcoming issue; Abu-Taha et al, 63 this issue), transcriptional complexes ( 64-69 ; Sharma et al, 70 Pandey and Robertson, 71 and Puts et al, 72 all in this issue), and components of signaling pathways of MAPK, [73][74][75] TGF-β [76][77][78] and Notch, 79 as well as other factors promoting invasion and metastasis ( 80,81 ; Ferrucci et al 82 upcoming issue). Accordingly, the list of protein/protein interactions involving NME1 is huge and could yield new information about the anti-metastatic activity of NME1, and more generally about the metastatic process.…”
Section: Nme In Metastasismentioning
confidence: 99%